دور العقد النفسي في بناء الهوية الاجتماعية للعاملين 1 دراسة تحليلية لأراء عينة من تدريسي الكليات الاهلية في محافظات الفرات الاوسط - احسان دهش جلاب; شروق عبد الرضا سعيد; زينب هادي معيوف الشريفي (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص هدفت هذه الد ا رسة إلى تحديد الدور الذي يؤديه العقد النفسي في بناء الهوية الاجتماعية للعاملين لدى عينة من تدريسيي الكليات الاهلية. وقد بلغ حجم العينة ( 248 ) تدريسياً موزعين على ( 11 ) كلية في ثلاثة محافظات هي (النجف الاشرف، كربلاء المقدسة، وبابل). ولاجل تحقيق هدف الد ا رسة صيغت فرضيتين رئيستين تم التحقق منهما من خلال عدد من الوسائل الاحصائية كالوسط الحسابي الموزون، والانح ا رف المعياري، ومعامل الارتباط و معادلة الانحدار. وبعد تحليل البيانات التي جمعت بواسطة اس تمارة الاستبيان التي تم اعدادها بالاعتماد على للهوية الاجتماعية للعاملين، (Blader&Tyler, للعقد النفسي ومقياس ( 2009 (Rousseau, مقياس ( 2000 توصلت الد ا رسة إلى عدد من الاستنتاجات لعل من ابرزها وجود اد ا رك واضح لدى عينة الد ا رسة حول مفاهيم الد ا رسة وان الت ا زم المنظمات بمضامين العقد النفسي من شأنه ان يعزز بناء الهوية الاجتماعية لدى عينة الد ا رسة. وانتهت الد ا رسة بعدد من التوصيات منها ضرورة سعي الكليات المدروسة إلى الالت ا زم بمضامين العقد النفسي لتعزيز الهوية الاجتماعية لدى التدريسيين فيها. الكلمات المفتاحية: العقد النفسي، الهوية الاجتماعية. Abstract. This study aimed to determine the role of the psychological contract in building the social identity of employees in a sample of professors of private colleges. The sample reached (248) professor distributed on (11) College in three governorates (Najaf, Karbala, and Babil). In order to achieve the goal of the study,two main hypotheses have been devised and verified through a number of statistical methods as the weighted mean, standard deviation, coefficient of correlation and regression equation. After the data was gathered by the questionnaire that had been prepared based on a scale (Rousseau,2000) for psychological contract and scale (Blader & Tyler, 2009) of the social identity of employees, the study reached a number of conclusions, perhaps the most prominent is the existence of a clear, understanding among the study sample concerning studying concepts. The psychological commitment of the organization to the contents of the contract would enhance the building of social identity among the study sample. The study is concluded with a number of recommendations, including the need that the studied colleges be commited to the contents of the psychological contract to enhance social identity among the professors . Key Words: Psychological contract, Social identity.